Public policies on healthcare-associated infections: a Brazil and UK case study - Padoveze, Maria Clara; Melo, Sara; Bishop, Simon; Poveda, Vanessa De Brito; Fortaleza, Carlos Magno Castelo Branco (Universidade de São Paulo, 2017)
To summarize the historical events and drivers underlying public policy for the prevention and control of healthcare-associated infections in Brazil and in the United Kingdom. In doing so, the article aims to identify lessons and recommendations for future development of public policy. The analysis is based on a historical overview of national healthcare-associated infections programs taken from previously published sources. Findings highlight how the development of healthcare-associated infections prevention and control policies followed similar trajectories in Brazil and the United Kingdom. This can be conceptualized around four sequential phases: Formation, Consolidation, Standardization, and Monitoring and Evaluation. However, while we identified similar phases of development in Brazil and the United Kingdom, it can be seen that the former entered each stage around 20 years after the latter.